Learning lessons: how listening makes us more local. Issue 2 (1st September 2011) - Ladds, Martyn; Davison, Steve
Abstract : At Sue Ryder we'd like to share what people told us about the way we communicate and the specialist palliative and end of life care we provide. We'd like to talk about the things people told us and the improvements we're now making. We asked what a specialist palliative and end of life care provider needs to do, to be better. After listening to what people told us, and looking at the health and social care sector, we're making visible changes in how people understand and experience our services. We'd like to share what we've learnt. The session will share research findings. Sources include: IPSOS MORI and service-users. We'll talk about how the experience of inpatient and day therapy services. We'll describe the way we're now communicating with service users, families and friends. We'll refer to case studies including the Department of Health funded capital scheme at Sue Ryder – Manorlands Hospice. We'll also share what how introducing new touch-screen technology, and the Information Standard, can help improve the quality and integrity of print and online communications. The session will cover lessons learnt, and how some assumptions were challenged. We'll show how listening is now helping us build a better future. Objectives: ▶ Share research evidence from IPSOS MORI, NOP, and service-users ▶ Case study the Department of Health capital scheme at Sue Ryder- Manorlands Hospice, Yorkshire ▶ Describe how we're increasing local engagement and identity ▶ Explain how new technologies and printed information can create better user experiences and assurance ▶ Describe how these lessons are influencing a new state of the art hospice facility at Peterborough, in Cambridgeshire (opens 2013).